Neuroinflammation and Neuromodulation in Neurological Diseases - Maria de los Angeles Robinson-Agramonte; Carlos-Alberto Gonçalves; Roberto Farina de Almeida; Alina González Quevedo; Sandra Chow; Luis Velázquez Pérez; Amado Díaz de la Fé; Patricia Sesterheim; Diogo Onofre Gomes Souza (Behavioral Sciences, 2019)
Neuroimmunology is a relatively young science. This discipline has emerged today from the research field as a mature and fully developed innovative research area that integrates not only pure topics of neuroimmunology, but also expands on wider fields such as neuroplasticity, neuronal reserve and neuromodulation in association with clinical events, amongst which behavioral disorders stand out. The Cuban School of Neuroimmunology—a recent meeting that took place in Havana, Cuba—focused on topics based on the molecular mechanisms of neuroinflammation in neurological disorders involving behavioral manifestations, such as multiple sclerosis (MS), autism, cerebellar ataxias, Alzheimer´s disease and stroke among others, as well as on the use of new interventional technologies in neurology. Professor Luis Velazquez, from the Cuban Academy of Sciences, dictated an interesting lecture on Spinocerebellar ataxias, a genetic disorder where recent hypotheses related to the influence of neuroinflammation as a neurobiological factor influencing the progression of this disease have emerged. At the same time, the use of new interventional technologies in neurology was discussed, including those referring to novel disease modifying therapies in the course of MS and the use of transcranial magnetic stimulation in several neurological diseases, the latter reinforcing how interventional strategies in the form of non-invasive bran stimulation can contribute to physical rehabilitation in neurology. This paper summarizes the highlights of the most relevant topics presented during the First Cuban School of Neuroimmunology, organized by the Cuban Network of Neuroimmunology, held in June 2019.